A survey of applications of multicriteria decision analysis methods in mine planning and related case studies. - Mahase, M.J.; Musingwini, C.; Nhleko, A.S. (The Southern African Institute of Mining and Metallurgy., 2016)
In an environment like the mining industry, which is characterized by different stakeholders with multiple objectives, multi-criteria decision analysis (MCDA) is a useful approach for optimal decision-making. The application of MCDA techniques in the mining industry has predominantly been in mine planning and related problems, although no comprehensive survey has previously been undertaken to establish the application trends. A survey of the use of MCDA techniques was therefore conducted using case studies from the literature. It was noted that often two or more methods are applied to the same problem in order to increase confidence in the solution derived. As the number of criteria and alternatives increases, some methods become inefficient. A combination of the analytic hierarchy process (AHP) method with other MCDA techniques was the most frequently used approach, indicating the efficiency of the AHP method, especially when evaluating problems with more criteria and fewer alternatives. A combination of fuzzy theory with AHP or other methods incorporates uncertainty. The findings from the survey will benefit users applying MCDA techniques to solve mine planning and related problems.
This study forms part of an MSc research project undertaken at the University of the Witwatersrand.
Keywords: Mine planning; Multi-criteria decision analysis (MCDA); Multi-criteria decision-making (MCDM); Multi-objective decision-making (MODM); Decision making; Analytic hierarchy process; Surveys; Mining industry